Time-Optimal Path Following for Robots With Convex-Concave Constraints Using Sequential Convex Programming - Debrouwere, Frederik; Van Loock, Wannes; Pipeleers, Goele; Dinh, Quoc Tran; Diehl, Moritz; De Schutter, Joris; Swevers, Jan (IEEE transactions on robotics, 2013)
Time-optimal path following considers the problem of moving along a predetermined geometric path in minimum time. In the case of a robotic manipulator with simplified constraints, a convex reformulation of this optimal control problem has been derived previously. However, many applications in robotics feature constraints such as velocity-dependent torque constraints or torque rate constraints that destroy the convexity. The present paper proposes an efficient sequential convex programming (SCP) approach to solve the corresponding nonconvex optimal control problems by writing the nonconvex constraints as a difference of convex (DC) functions, resulting in convex-concave constraints. We consider seven practical applications that fit into the proposed framework even when mutually combined, illustrating the flexibility and practicality of the proposed framework. Furthermore, numerical simulations for some typical applications illustrate the fast convergence of the proposed method in only a few SCP iterations, confirming the efficiency of the proposed framework.